Borderland religion : ambiguous practices of difference, hope and beyond - Turner, Bryan S.; Wyller, Trygve Eiliv; Machado, Daisy L.; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
Borderland Religion narrates, presents and interprets the fascinating and significant practices when borders, migrants and religion intersect. This collection of original essays combines theology, philosophy and sociology to examine diverse religious issues surrounding external national borders and internal domestic borders as these are challenged by the unstoppable flow of documented and undocumented migrants. While many studies of migration have examined how religion plays a major role in the assimilation and integration of waves of migration, this volume looks at a number of empirical studies of how emergent religious practices arise around border crossings.Contributions of scholars from a broad range of disciplines ensure a careful analysis of this highly topical situation. The volume s interdisciplinary profile will appeal to scholars and students in religious studies, migration studies, theology and citizenship studies.The volume begins with a detailed analysis of the borderland religion context and research. The aim is to bring an eschatological interpretation of the borderland religion, its impact and significance for migrants. Themes include a critical analysis of how religion has formatted Europe; empirical studies from the US/Mexican border and Southern Africa; an overview of the European refugee crisis in 2015; editors account of borderland religion from the perspective of citizenship studies.
part PART I Introduction -- r TRYGVE WYLLER -- chapter 8 A postcolonial perspective on religion and migration / FEDERICO SETTLER -- part PART IV Siding with the powerless -- chapter 9 Religion-making in the border space and by border land / HANS-JOACHIM SANDER -- chapter 10 The boy on the beach: The photographic event that contested the violence of European governmentality / MADS PETER KARLSEN, BENT MEIER SØRENSEN AND KASPAR VILLADSEN -- chapter 11 Conclusion: Impacting religions, impacting societies / DAISY L. MACHADO.
Keywords: Boundaries; Emigration and immigration -- Religious aspects; Ethnicity -- Religious aspects; Identification (Religion); Religion and geography; Religion; Identification (Religion); SOCIAL SCIENCE / Sociology / General